STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR NEGERI TERAKREDITASI A KOTA PALU - Tandea, Melki Sedik; Mega Hariani, Ni Made; Kertayasa, I Ketut (JATMIKA : Journal Education and Learning of Elementary School, 2025)
The results of observations when conducting initial observations in three public elementary schools, researchers saw that the teachers in the three schools had good competence, especially in the learning process in the classroom, several teachers the three schools were driving teachers. This is because there is a good leadership strategy carried out by the principal in carrying out his duties at school. Based on this, the researcher was interested in conducting research in 15 public elementary schools with the aim of determining the principal's leadership strategy in improving teacher performance in accredited A Public Elementary Schools Palu City. The method used in this study is a qualitative descriptive method. The results of the study showed that the principal of the Accredited A Public Elementary School Palu City has strategies used to improve teacher performance, namely: implementing discipline, conducting assessments on the Merdeka Mengajar Platform (PMM), conducting evaluations, holding supervision programs, holding training (workshops) and implementing a joint leadership system. Some of the obstacles faced by principals in improving teacher performance are: teachers who are not disciplined in carrying out their duties at school, a changing system of rules, limited budget and teachers who feel they are in a comfort zone.